The value of implementation science in bridging the evidence gap in bereavement care - Breen, Lauren; Moullin, Joanna (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2022)
There is a gap in the use of evidence in bereavement care. Implementation science is a field focused on moving evidence into practice and therefore may help close the gap. Implementation science advances the design, relevance, and dissemination of research and the adoption, implementation, and maintenance of evidence-based practices. We provide an overview of implementation science, describe five implementation frameworks (Knowledge to Action; Behavior Change Wheel; Exploration Preparation Implementation Sustainment; Interactive Systems Framework; and Reach, Adoption, Implementation, Maintenance), and illustrate their application in bereavement care. These advancements will promote high-quality bereavement care that improves the lives of bereaved people.